2018
DOI: 10.1186/s12873-018-0177-2
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and safety outcomes - a cross-sectional nationwide survey of EMS-workers in Germany

Abstract: BackgroundThe association between burnout and patient safety has been analyzed in many studies for nurses, physicians, and residents. However, studies concerning prehospital emergency medical services (EMS) workers are limited, although they are particularly under risk for emotional stress. This study aims to descriptively analyze the overall degree of burnout among EMS-workers, and potential adverse events that might harm patients as well as the relationship between burnout and perceived safety outcomes for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 40 publications
3
51
0
15
Order By: Relevance
“…The MBI-EE and DP scores of the HCWs who had children included in our study were significantly higher. The fact that MBI-EE is less common among those who have children is a finding highlighted in previous studies (27,28). In our study, we thought that HCWs, who have children at home, who live with a family member over 65 years old and/or who have a chronic illness living in their homes, maybe a reason that increases the level of fear, anxiety and burnout of these people.…”
Section: Discussionsupporting
confidence: 49%
“…The MBI-EE and DP scores of the HCWs who had children included in our study were significantly higher. The fact that MBI-EE is less common among those who have children is a finding highlighted in previous studies (27,28). In our study, we thought that HCWs, who have children at home, who live with a family member over 65 years old and/or who have a chronic illness living in their homes, maybe a reason that increases the level of fear, anxiety and burnout of these people.…”
Section: Discussionsupporting
confidence: 49%
“…Laschinger, Borgogni, Consiglio, and Read () found that when nurses experience the syndrome of burnout, it can significantly influence their physical, psychological and mental health in negative terms. Additionally, when nurses are exposed to a high rate of burnout, it can lead to several negative outcomes for healthcare organisations (Adriaenssens, De Gucht, & Maes, ), such as reduced quality of nursing care (Liu & Aungsuroch, ), an increased expressed intention to leave (Chang et al, ), absenteeism (Suñer‐Soler et al, ) and alarmingly compromised patient safety (Baier, Roth, Felgner, & Henschke, ). Maslach () stated that burnout is an event that results from cumulative effects in stressful workplaces.…”
Section: Introductionmentioning
confidence: 99%
“…EMTs who are experiencing burnout had almost 4 times the odds of planning to quit within one year relative to those who are not experiencing burnout. This association is present throughout burnout literature thereby linking burnout and employee turnover [18,26,48,51,52]. With its strong association, interventions to decrease EMT burnout and improve EMT wellness may be a modifiable risk factor to decrease employee turnover and address workforce shortages.…”
Section: Plos Onementioning
confidence: 97%
“…For data requests, please contact the ethics committee below and cite IRB#41940. Stanford dissatisfaction [23][24][25][26]. Burnout in medical personnel has even been associated with the theft of medications and supplies [27].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation